2007
DOI: 10.1097/mao.0b013e318033f020
|View full text |Cite
|
Sign up to set email alerts
|

Important Factors for the Hearing Loss Caused by the Triple Semicircular Canal Occlusion in Guinea Pigs

Abstract: Hearing loss caused by TSCO can be greatly reduced by avoiding damage to the membranous labyrinth and by shortening the operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…Animal studies showed that various hearing impairments have been documented after TSCO, while single semicircular canal occlusion has been recognized as an efficient method of eliminating vertigo without causing a significant hearing impairment. 16 Meanwhile, in our animal models, the symptoms and compensatory period after USSCO were all similar to what have been reported in patients of intractable BPPV (benign paroxysmal positional vertigo) after surgery, which could improve imbalance symptoms in 94% of patients. 2 The model used in this experiment was proved to be simple and stable and could thus be used for the studies of the mechanisms of vestibular central compensation and acute unilateral peripheral vestibular lesion.…”
Section: Changes Of Behaviour and Eng After Unilateral Horizontal Sem...supporting
confidence: 86%
“…Animal studies showed that various hearing impairments have been documented after TSCO, while single semicircular canal occlusion has been recognized as an efficient method of eliminating vertigo without causing a significant hearing impairment. 16 Meanwhile, in our animal models, the symptoms and compensatory period after USSCO were all similar to what have been reported in patients of intractable BPPV (benign paroxysmal positional vertigo) after surgery, which could improve imbalance symptoms in 94% of patients. 2 The model used in this experiment was proved to be simple and stable and could thus be used for the studies of the mechanisms of vestibular central compensation and acute unilateral peripheral vestibular lesion.…”
Section: Changes Of Behaviour and Eng After Unilateral Horizontal Sem...supporting
confidence: 86%
“…Therefore, beyond the mechanism of mechanical obstruction, further studies are required to explore the complex pathophysiological mechanisms of this phenomenon. Notably, TSCO can cause hearing loss of up to 30%, which may be associated with labyrinthitis and perilymph fistulae ( 10 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…TSCO was then performed as follows: A fenestration of about 2 mm was made in the central portion of the bony canal, as far away as possible from the ampulla, using a 1-mm drill and a hook to pry off the bone, without opening the endosteum or the membranous labyrinth. Great care was taken to avoid injuring the membranous labyrinth as it can lead to serious hearing loss ( 10 ). The temporalis fascia, bone dust collected during the procedure, and fibrinogen glue were inserted through the fenestra to compress the endosteum and membranous labyrinth against the bony back wall.…”
Section: Case Reportmentioning
confidence: 99%
“…Opening and plugging an SSC, with or without opening the membranous labyrinth, carries a definite risk of sensorineural hearing loss, even in noninflamed, noninfectious ears, as documented by reports on use of the surgical technique in cases of SSC dehiscence 18 and by animal studies. 19 Moreover, opening the SSC in an inflamed ear with chole steatoma could enhance the risk of labyrinthitis and its ensuing sensorineural hearing loss. In selected cases, our technique provides fairly good visibility and offers excellent odds for hearing preservation, because the membranous labyrinth remains untouched.…”
Section: Discussionmentioning
confidence: 99%